HUBUNGAN POLA KONSUMSI MAKANAN DAN KONSUMSI SUSU DENGAN TINGGI BADAN ANAK USIA 6-12 TAHUN DI SDN 173538 BALIGE - Ria Solia Nainggolan; Evawany Yunita Aritonang; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACT Primary student is an investment the nation because children that age are the future generation. Nutrition becomes important for primary student because it can support the growth physically. Consumption of food and milk of children 6-12 years old can help the nutritional optimally to support the child's growth in height. The objective of this study was to know the relationship between food and milk consumption with body height of children 6-12 years old in SDN 173538 Balige (consist of 60 children as samples). Design of study was cross sectional study. The study was conducted by calculating the adequacy of energy, protein, and calcium from food and milk consumption of children using 24 hour food recall method. Child’s body height was measured by microtoise instrument. The result of study showed that in general, child's body height by age is 81.7% in normal category, 16,7% in short category, and 1,7% in stunting category. There was a significant relationship between the adequacy protein of food, the adequacy protein and calcium of milk with body height. While there was no relationship the adequacy energy and calcium of food and the adequacy energy of milk with body height. The school suggested to cooperate with Balige Health Center provide education to primary student about daily nutrition and benefits of drink milk for height growth. Parents should also pay more attention to children’s food consumption in terms of quantity. Keywords: Food consumption, milk consumption, body height, primary student